Infusing Learners' Problem-Solving Skills Through Problem-Based Learning Model Assisted Socio-Scientific Issues (SSI) Worksheet on Environmental Pollution - Tariza Putri Alpianti, Neng; Nor Amelia, Rizki (JPPS (Jurnal Penelitian Pendidikan Sains), 2024)
Problem-solving skills are an essential part of science learning because these skills guide students in discovering science concepts to make learning more meaningful. Objectives: This study aims to test whether there is a significant difference in students' problem-solving skills before and after the application of the Problem-Based Learning Model assisted by the Socio-Scientific Issues (SSI) Worksheet and test whether there is a significant difference in the improvement of students' problem-solving skills between the experimental class and the control class. Method:  This study applied the pre-test-post-test control group design on two classes (64 students) taken by cluster random sampling. Data collection techniques in this research used observation, interviews, tests, and documentation methods. Then, the data obtained was analyzed using the homogeneity test, normality test, dependent t-test, independent t-test, and N - Gain test. The instrument used was a problem-solving test in the form of an essay proven to have good psychometric characteristics. Results:  The results showed a significant difference in students' problem-solving skills before and after applying the Problem-Based Learning Model assisted by the Socio-Scientific Issues (SSI) Worksheet. There was a significant difference in improving students' problem-solving skills between the experimental class (N-Gain high category) and the control class (N-Gain medium category). Thus, the SSI Worksheet integrated into the PBL model effectively improves students' problem-solving skills. Novelty: Previous research has not used SSI Worksheets integrated into the PBL model to train students' problem-solving skills.